Adult consequences of late adolescent alcohol consumption: a systematic review of cohort studies. - Jim McCambridge; John McAlaney; Richard Rowe (PLoS Medicine)
Background Although important to public policy, there have been no rigorous evidence syntheses of the long-term consequences of late adolescent drinking. Methods and findings This systematic review summarises evidence from general population cohort studies of drinking between 15-19 years old and any subsequent outcomes aged 20 or greater, with at least 3 years of follow-up study. Fifty-four studies were included, of which 35 were assessed to be vulnerable to bias and/or confounding. The principal findings are: (1) There is consistent evidence that higher alcohol consumption in late adolescence continues into adulthood and is also associated with alcohol problems including dependence; (2) Although a number of studies suggest links to adult physical and mental health and social consequences, existing evidence is of insufficient quality to warrant causal inferences at this stage. Conclusions There is an urgent need for high quality long-term prospective cohort studies in order to better understand the public health burden that is consequent on late adolescent drinking, both in relation to adult drinking and more broadly. Reducing drinking during late adolescence is likely to be important for preventing long-term adverse consequences as well as protecting against more immediate harms. Please see later in the article for the Editors' Summary.